PERUBAHAN ADAT MERARIQ PADA ERA GLOBALISASI DI KELURAHAN LENENG, NUSA TENGGARA BARAT - Darmayanti, Arni; Kebayantini, Ni Luh Nyoman; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRAK Merariq (Elope) has been a culture for Sasak society. It has special meaning that is to respect a women that cannot be equalized with a thing, furthermore as a character form being a gentleman that able to take care of his wife. But it has been reformatted. A several societies don’t use Merariq but they use purposing to purpose their wife to be as commonly used by most of man that want to marry his woman. Which is this also happened to society in Leneng Village, NTB. The issue that studied in this project is: 1). How is the process of Merariq in this globalization era?, 2). what is the effect of reformation of the Merariq? . The aim of this research is to answer those issues with applying case study approach furthermore uses qualitative method. The theory that used is social changed (functional) from William F. Ogburn. The result of this research illustrates that Merariq is one of the wedding process of Sasak culture that has reformatted from several other wedding process. The Sasak wedding process are merariq, merangkat, mesejati, nyelabar/ selabar, bait wali, ngawinang, sorongserah, begawe, nyongkolan and bales ones nae. From those processes, several of them that have been reformatted are merariq, nyelabar, sorongserah, begawe, and nyongkolan. This reformation causes both negative and positive effect for the society. The positive effect is reducing early marriage number and reducing conflict that caused by the Merariq. In another hand, the negative effect makes a gap among society’s relationship. Keywords: ‘Merariq’ Tradition, Social Changed, Globalization